Pengaruh takaran biochar dan pupuk kandang ayam terhadap pertumbuhan dan hasil tanaman bayam (amaranthus tricolor l.) - NABU, MARIYANI E; Neonbeni, Eduardus Y (Savana Cendana, 2025)
ABSTRACT This study aims to determine the effect of Biochar dose and chicken manure on the growth and yield of spinach plants. This research was carried out in October 2019 - November 2019 in the Experimental Field of the Faculty of Agriculture, University of Timor. By using the Complete Design (CRD) 2 factors 3x3 which was repeated 5 times. The first factor is rice husk biochar (B) consisting of 3 (three) levels, namely: (B0) Without biochar (B1) 2.25 t / ha, (B2). 5 t / ha. The second factor is chicken manure (J) consisting of 3 (three) levels, namely: (J0) Without chicken manure, (J1). Chicken manure 2.25 t / ha, (J2) Chicken manure 5 t / ha. on the dose of chicken manure J1 (2.25 t / Ha) has a significant effect on increasing yield of spinach on the parameters of fresh plant weight and plant wet weight. The dose of biochar and dose of chicken manure are very significant for the growth of spinach, on the parameters of plant height, number of leaves and stem diameter.